Remediation of Arsenic by Metal/ Metal Oxide Based Nanocomposites/ Nanohybrids: Contamination Scenario in Groundwater, Practical Challenges, and Future Perspectives. Issue 3 (3rd July 2021) - Kumar, Ajay; Joshi, Himanshu; Kumar, Anil
ABSTRACT: Arsenic is a global concern as a groundwater contaminant due to its severe health consequences. Its removal employing nano adsorbents in both ex-situ and in-situ modes has gained attention among the scientific community from the past two and a half decades. Nanotechnology-based water treatment systems are a logical choice concerning resources and energy efficiency. The literature contains many cases in which several nanoadsorbents were used for arsenic removal. This review attempts to classify a variety of used nanoadsorbents according to their polymorphic structure and stability features, assessing the nature and modality of the bench-scale studies, identifying the removal mechanisms, and exploring further approaches for potential field-scale applications. A methodology to calculate the production cost of nanoadsorbents at a laboratory scale is also proposed.